Anthropogenic forcings on the climate of the Aral Sea: A regional modeling perspective. (December 2017) - McDermid, Sonali Shukla; Winter, Jonathan
Highlights: The ongoing Aral Sea desiccation and near-disappearance may further exacerbate anthropogenic climate change. The Aral Sea removal (akin to the near-loss in summer 2014) results in a 2 °C–6 °C temperature increase during the summer. The Aral Sea removal enhanced net LW radiation and sensible heat, reduced ET, changing regional energy and moisture balances. Model simulations of the ongoing desiccation with GHG-induced warming will help better represent regional climate changes. Abstract: The Aral Sea was formerly one of the world's largest lakes and supported critical ecosystem services, fisheries, and major shipping routes. It was also situated in a rapidly industrializing agricultural region and, as such, multiple anthropogenic forcings have modified the Aral's regional environmental conditions over the latter 20th century. In particular, rising atmospheric greenhouse gas (GHG) concentrations coupled with intensive water resource use have had significant regional climate impacts. Sustained abstractions from regional rivers as an irrigation resource for intensified agricultural production has led to the rapid desiccation of the Aral Sea. As of summer 2014, only 10% of its historic extent remained. This paper reports modeling experiments to elucidate the climatic changes resulting from both increased GHG concentrations and an idealized disappearance of the Aral Sea. We utilized the MIT Regional Climate Model to perform 30-year experiments of pre-desiccated and fully desiccated Aral Sea conditions under moderate and enhanced GHG forcings. Complete desiccation combined with the GHG forcings resulted in substantial increases in summertime net longwave radiation, sensible heating, and surface temperature. Additionally, large reductions in evapotranspiration altered the regional soil moisture − surface temperature relationship. Furthermore, a completely desiccated Aral Sea heightened the GHG-induced regional warming. These results demonstrate how a total loss of the Aral Sea might exacerbate regional climate change. At the same time, they suggest that some of the regional warming and moisture regime shifts could be alleviated with the Aral Sea's restoration, requiring the implementation of conservation practices and improved regional water governance.